Α-Synuclein Drives Tau S Cytotoxic Aggregates Formation Through Hydrophobic Interactions - Melo-Hurtado, F; Caballero-Alvial, L (John Wiley and Sons Inc, 2023)
Tau and α-synuclein are proteins involved in pathologies known as tauopathies and synucleinopathies, respectively. Moreover, evidence shows that there is a crosstalk between them as is seen in the brains of individuals with sporadic neurodegenerative disorders. Based on that, we present data showing that the hydrophobic α-peptide 71VTGVTAVAQKTV82 induces the aggregation of the full-length tau fragment in the absence of heparin assessed by ThT. Moreover, AFM images reveal the presence of straight filaments and amorphous aggregates of full-length tau in the presence of the α-peptide. Additionally, ITC experiments showed the interaction of the α-peptide with tau full-length (441 amino acids),4R (amino acids from 244 to 369), and both hexapeptides 275VQIINK280 and 306VQIVYK311 through hydrophobic interactions. The Raman spectroscopy spectra showed conformational changes in the Amide region in the aggregates formed with full-length tau and α-syn peptide. Furthermore, the incubation of extracellular aggregates with N2a cells showed morphological differences in the cellular body and the nucleus suggesting cell death. Moreover,, the incubation of different types of aggregates in cell culture provokes the release of Lactate dehydrogenase (LDH). Altogether, we found that α-synuclein peptide can drive the aggregation of full-length tau-provoking morphological and structural changes evoking cytotoxic effects. © 2023 Wiley-VCH GmbH.